Waste Analysis Number for Warehouse Operations - Yelmakova, Amina; Martínez, Felipe; Vinš, Marek; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This paper presents the use of Failure Modes and Effects Analysis (FMEA) as a methodology to find possible areas for improvement in the picking process. The study aims to identify issues and provide suitable solutions, including applying Lean tools and Failure Modes and Effects Analysis (FMEA) methodologies. The study uses a qualitative and quantitative information-gathering strategy based on a survey and interviews to assess risk and identify the main issues in the picking process. The practical part presents an analysis of the picking process in one of the warehouses of Company A through the SIPOC methodology, identifying the main errors during the picking process and the types of waste to which they relate and an assessment from the respondents. The results of the bachelor thesis show the application of Failure Modes and Effects Analysis (FMEA) in the picking process of one of the warehouses of Company A and suggest ways of improvement to achieve lower risks through 5S, Kaizen (PDCA), and Total Productive Maintenance (TPM).
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses